Public Perception of the Quality of Motor Vehicle Tax Payment Services - Ritonga, Bima Ari Agustian; Simanjorang, Elida Florentina Sinaga; Siregar, Marlina (Almana : Jurnal Manajemen dan Bisnis, 2023)
Payment of motorized vehicle tax is an obligation that must be fulfilled by every vehicle owner as a contribution to the country's development. The Samsat Office is a government agency responsible for administering motor vehicle taxes. The Samsat Village Tax Outlet Office has an important role in assisting motorized vehicle owners to fulfill their vehicle tax payment administration as well as an effort to increase tax revenue, especially in the area around the Samsat outlet office. This research was conducted to find out the public's perception of the quality of service for paying motor vehicle tax at the Samsat Office of the Village Tax Office so that it can provide recommendations for appropriate improvements to increase public satisfaction and compliance in paying motor vehicle tax. This type of research is descriptive research with qualitative and interpretive data analysis techniques. The number of samples is 100 people which is determined based on the Wibisono formula. From the results of this study, it can be seen that the public's perception of the quality of motor vehicle tax payment services at the Village Samsat Tax Office outlet through the Physical Evidence parameter, the Reliability parameter, the Responsiveness parameter, the Assurance parameter, and the Empathy parameter is Good.